Why Wages Don't Fall in Jobs with Incomplete Contracts - Marco Fongoni; Daniel Schaefer; Carl Singleton (Institute of Labor Economics (IZA), 2024)
We investigate how the incompleteness of an employment contract - discretionary and non-contractible effort - can affect an employer's decision about cutting nominal wages. Using matched employer-employee payroll data from Great Britain, linked to a survey of managers, we find support for the main predictions of a stylised theoretical framework of wage determination: nominal cuts are at most half as likely when managers believe their employees have significant discretion over how they do their work, though the involvement of employees, via information sharing, reduces this correlation. We also describe how contract incompleteness and wage cuts vary across different jobs. These findings provide the first observational quantitative evidence that managerial beliefs about contractual incompleteness can account for their hesitancy over nominal wage cuts. This has long been conjectured by economists based on anecdotes, qualitative surveys, and laboratory and field experiments.
Keywords: E24; E70; J31; J41; 330; wage rigidity; employment contract; workplace relations; employer-employee data